Antimicrobial susceptibility patterns of Ureaplasma species and Mycoplasma hominis in pregnant women - Redelinghuys, Mathys J (BioMed Central, 2014)
BACKGROUND: Genital mycoplasmas colonise up to 80% of sexually mature women and may invade the amniotic cavity during pregnancy and cause complications. Tetracyclines and fluoroquinolones are contraindicated in pregnancy and erythromycin is often used to treat patients. However, increasing resistance to common antimicrobial agents is widely reported. The purpose of this study was to investigate antimicrobial susceptibility patterns of genital mycoplasmas in pregnant women. METHODS: Self-collected vaginal swabs were obtained from 96 pregnant women attending an antenatal clinic in Gauteng, South Africa. Specimens were screened with the Mycofast Revolution assay for the presence of Ureaplasma species and Mycoplasma hominis. The antimicrobial susceptibility to levofloxacin, moxifloxacin, erythromycin, clindamycin and tetracycline were determined at various breakpoints. A multiplex polymerase chain reaction assay was used to speciate Ureaplasma positive specimens as either U. parvum or U. urealyticum. RESULTS: Seventy-six percent (73/96) of specimens contained Ureaplasma spp., while 39.7% (29/73) of Ureaplasma positive specimens were also positive for M. hominis. Susceptibilities of Ureaplasma spp. to levofloxacin and moxifloxacin were 59% (26/44) and 98% (43/44) respectively. Mixed isolates (Ureaplasma species and M. hominis) were highly resistant to erythromycin and tetracycline (both 97% resistance). Resistance of Ureaplasma spp. to erythromycin was 80% (35/44) and tetracycline resistance was detected in 73% (32/44) of Ureaplasma spp. Speciation indicated that U. parvum was the predominant Ureaplasma spp. conferring antimicrobial resistance. CONCLUSIONS: Treatment options for genital mycoplasma infections are becoming limited. More elaborative studies are needed to elucidate the diverse antimicrobial susceptibility patterns found in this study when compared to similar studies. To prevent complications in pregnant women, the foetus and the neonate, routine screening for the presence of genital mycoplasmas is recommended. In addition, it is recommended that antimicrobial susceptibility patterns are determined.